Development and Technical Performance Evaluation of Mobile Goods Delivery Tracking System Using User Acceptance Testing - Fatmariani Fatmariani; Eka Hartati; Rendy Almaheri Adhi Pratama; Muhammad Jhonsen Syaftriandi; Wizayunifa Wizayunifa (Politeknik Ganesha Medan, 2026)
The rapid growth of digital logistics services has increased the demand for mobile-based parcel tracking systems capable of providing real-time, accurate, and accessible shipment information. Most previous studies have primarily focused on developing web-based applications and conducting functional testing, while studies integrating technical performance evaluation with user acceptance assessment remain limited. This study aims to evaluate the technical performance and user acceptance of a mobile-based parcel tracking system. The system was developed using the Waterfall software development model. Functional verification was conducted through Black Box Testing, while user acceptance was evaluated using User Acceptance Testing (UAT) involving 82 respondents, including administrators, couriers, members, and customer service personnel. The UAT instrument consisted of 15 assessment indicators measured using a five-point Likert scale. In addition, technical performance was assessed by measuring system latency, throughput, and mobile device resource utilization. The results demonstrate that all system functionalities operated according to user requirements. The application achieved an average latency of 1.50 seconds, throughput of up to 45 requests per minute, 18% CPU utilization, 145 MB RAM consumption, 4% battery usage per 30 minutes, and 2.8 MB of network data usage per session, indicating that the system performs efficiently and responsively on mobile devices. The UAT evaluation yielded an overall acceptance score of 87.43%, categorized as highly acceptable, confirming that users positively perceived the system in terms of usability, tracking information clarity, operational efficiency, and support for logistics delivery activities. These findings provide empirical evidence that integrating technical performance evaluation with user acceptance assessment offers a comprehensive framework for developing mobile-based parcel tracking systems that are responsive, resource-efficient, and aligned with operational requirements in digital logistics services.